METHOD OF MEASUREMENT OF STRENGTH OF CORE CASTING PAINT AT HIGH TEMPERATURES - O. S. Komarov; V. M. Nemenenok; T. D. Komarova (Литьë и металлургия)
The method and device for measuring of the strength of the core casting refractory paint at high temperatures were developed. It has been shown that the failure strength sodium aluminates binder after testified that decrease of sodium aluminates binder strength after being in the range of 300–600 °C is lower than that for sodium silicate. There is a correlation between hardness and strength of the paint during heating at 1300 °C.